The Effect of Der and Risk on Stock Return on Consumer Goods Companies - Yelsha Dwi Pasca (Return : Study of Management, Economic and Bussines, 2022)
Background: In the capital market, the stock price of a company can be used as a measure of whether or not the company's financial performance is good so it can be said that under reasonable and normal conditions, an increase in the financial performance of a company, its share price also increases or increases. Aim: to find out (1) the effect of the Debt to Equity Ratio on Stock Returns in Consumer Goods Companies listed on the Indonesia Stock Exchange in 2016-2019, (2) the effect of Risk on Stock Returns in Consumer Goods Companies listed on the Indonesia Stock Exchange in 2016-2019, and (3) the simultaneous effect of Debt to Equity Ratio and Risk on Stock Returns in Consumer Goods Companies listed on the Indonesia Stock Exchange 2016-2019. Method: This study uses descriptive and verification methods with a quantitative approach. Findings: Based on hypothesis testing using the t-test, it is concluded that the partial debt to equity ratio has a positive and insignificant effect on stock returns, while risk has a positive and significant effect on stock returns. Based on the F test, it is concluded that simultaneously debt to equity ratio and risk have a positive and significant effect on stock returns. Several things can be used as input for investors to pay more attention to the analysis of debt to equity and the systematic risk of the shares to be purchased. So that investors can predict and provide an overview of which stocks will provide returns that are in line with investor expectations